2014
DOI: 10.1109/tcyb.2014.2311824
|View full text |Cite
|
Sign up to set email alerts
|

Composite Neural Dynamic Surface Control of a Class of Uncertain Nonlinear Systems in Strict-Feedback Form

Abstract: This paper studies the composite adaptive tracking control for a class of uncertain nonlinear systems in strict-feedback form. Dynamic surface control technique is incorporated into radial-basis-function neural networks (NNs)-based control framework to eliminate the problem of explosion of complexity. To avoid the analytic computation, the command filter is employed to produce the command signals and their derivatives. Different from directly toward the asymptotic tracking, the accuracy of the identified neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
166
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 349 publications
(166 citation statements)
references
References 43 publications
0
166
0
Order By: Relevance
“…An experiment on a quasi-motorcycle testing rig validated the efficacy of this control strategy. In [55], a neural dynamic control was incorporated into the strict-feedback control of a class of unknown nonlinear systems by using the dynamic surface control technique. For a class of uncertain nonlinear systems with unknown hysteresis, NN was used for compensation of the nonlinearities [56].…”
Section: Cerebellar Model Articulation Controller (Cmac) Nnmentioning
confidence: 99%
“…An experiment on a quasi-motorcycle testing rig validated the efficacy of this control strategy. In [55], a neural dynamic control was incorporated into the strict-feedback control of a class of unknown nonlinear systems by using the dynamic surface control technique. For a class of uncertain nonlinear systems with unknown hysteresis, NN was used for compensation of the nonlinearities [56].…”
Section: Cerebellar Model Articulation Controller (Cmac) Nnmentioning
confidence: 99%
“…In [9,10], the NN is used to approximate several random perturbations and unknown functions. In [11][12][13][14][15][16], several nonlinear system solutions are studied based on neural networks and fuzzy logic systems. In [17], adaptive control schemes based on neural networks were proposed for nonlinear systems with unknown functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, usually it is not possible to derive the signal directly. In [1], with the output redefinition, the composite learning [22] is proposed with the serial-parallel estimation model. It is shown that the obtained predictor error can highly enhance the update of the learning system.…”
Section: Introductionmentioning
confidence: 99%